Pengaruh Durasi Aplikasi Bahan Adhesif Self-Etch Terhadap Kebocoran Mikro pada Tumpatan Resin Komposit Kelas V - Hapsari, Rani Indri; , drg. Noor Hafida Widyastuti, Sp.KG; , drg. Nanang Krisnawan (2015)
Microleakage was one of the major concerns associated with composite restoration. One of the ways to prevent microleakage was prolonged self-etch adhesive application time. The aim of this study was to evaluate the effect of selfetch adhesive application time on microleakage class V composite restoration. This research was a laboratory experimental study using posttest only control group design. 27 premolar teeth were prepared for class V cavity and were divided into 3 self-etch adhesive application time groups: group I (20 seconds), group 30 (30 seconds), and group III (40 seconds), then cured by light curing and the cavities were restored with composite resin. Specimens were thermocycled, immersed in methylene blue 2% then centrifuged. Teeth were sectioned and evaluated using a stereomicroscope at 120x magnification. Statistical analysis was performed with Kruskal-Wallis (p<0,05) and Mann-Whitney test. The results showed that there was no significant different between group I & II. Significant difference was seen between group II&III and group I&III. Conclusion: self-etch adhesive application time had effect on microleakage class V composite restoration.